Analysis of Cryptocurrency, Bitcoin and the Future - Manjula.B.C; Shilpa.B.S; Sundaresh. M (PT FORMOSA CENDEKIA GLOBAL, 2022)
Technology advances at a rapid rate, and the success of a given technology is almost solely dictated by the market upon which it seeks to improve. Cryptocurrencies may revolutionize digital trade markets by creating a free flowing trading system without fee. The rapid development and growth in the field of information and communication technologies has changed our day to day life. Not only day to day it has changed our traditional pattern of banking and financial transactions. This advancement of information communication technology has helps to use of paper work activities into digital operations. The upgraded technologies have also changed the pattern of financial transactions as well as created a new form of money. Cryptocurrencies are not likely to replace traditional fiat currency, they could change the way internet connected global markets interact with each other, clearing away barriers surrounding normative national currencies and exchange rates. Cryptocurrencies may revolutionize digital trade markets by creating a free flowing trading system without fees. Bitcoin is presented which illuminates some of the recent events and movements that could influence whether bitcoin contributes to a shift in economic paradigms.